Building immigrants’ solidarity with police: procedural justice, identity and immigrants’ willingness to cooperate with police - Murphy, Kristina (The British journal of criminology, 2022)
Some immigrants can be reluctant to cooperate with the police due to experiences of social exclusion and discrimination. Procedural justice scholars argue that people cooperate with police when they feel the police are just and fair because such treatment motivates identification with social categories that police represent. In this paper, we consider whether immigrants in Australia respond favourably to procedurally just treatment from police because it enhances their identification with both Australia and the police. Using survey data from 903 Vietnamese, Middle Eastern and British immigrants, we demonstrate an association between police procedural justice and both modes of identification. We also find that both identities mediate the relationship between procedural justice and cooperation. The implications of these findings are discussed.